New methods for gathering the spatial data from land consolidation project - Mária Leitmanová; Jaroslav Bažík; Zlatica Muchová (Acta Scientiarum Polonorum. Formatio Circumiectus)
Land consolidation projects in the Slovak Republic have reached the state where there is sufficient sample of valuable information (planimetric and hypsographic measurements, updated maps of estimated pedologic-ecological units, concepts of local territorial system of ecological stability, plans for the general principles of functional organization of the territory, etc.) for society. The contribution points out need to create a uniform public or archiving information system (database), which is incurred in landscape planning activities in model areas. By now several information systems created in Slovakia are not connected one to another and thus cannot be further use. The article pointed out the procedures leading to the processing of a unified information system that collects and archives the outputs of landscaping activities in the area. This is dedicated to the administrators, system users and use cases of the unified system. Therefore we emphasized the importance of system deployment defined for different users. Next step is to describe the input to the elaboration of a comprehensive database. The system is demonstrated on the basis of data obtained from land consolidation projects. Subsequently, we present all computed graphical information by publishing on the local console of OpenGeoSuite environment.